Cyber Crime E-Commerce Business Transactions - Lubis, Fauziah (SASI, 2022)
Introduction: Law enforcement and protection for cyber cases is focused on consumers as victims of digital crimes where consumers are generally harmed when conducting business transactions digitally.  Where the focus of this paper discusses the legal protection of victims of cybercrime victims when transacting business.Purposes of the Research: The purpose of this study is to explain the concept of cybercrime in financial transactions.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: Cyber crime is currently very growing in Indonesia, especially in the current era of digitalization. Where the law can protect from new crimes that live in the current kekininia period so that victims of cyber crime legally in Indonesia can be implemented in accordance with its purpose, which is to protect all Indonesian people from crime cases.